‘CITTASLOW’: AN ALTERNATIVE MODEL FOR LOCAL SUSTAINABLE DEVELOPMENT OR JUST A MYTH? EMPIRICAL EVIDENCE IN THE CASE OF TARAKLI (TURKEY) - İlhan, Öznur Akgiş and Karakaş, Erdal and Özkaraman, Büşra (Quaestiones Geographicae, 2020)
This research attempts to answer whether Cittaslow is a myth or an effective model for development for Taraklı, a small town in the Sakarya province of Turkey. The study was designed and analysed using the mixed method research model. The results are as follows. Since Taraklı became a Cittaslow, the number of tourists increased which ultimately helped to fight against unemployment and also increased income of people. Women’s participation in the labour force had increased and their representation in public places was enhanced. Important steps were taken towards the preservation of cultural heritage. Along with quantitative and qualitative improvements in green areas, the local people’s awareness of environmental protection has increased.